1986
DOI: 10.1029/jb091ib10p10337
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic structure of the upper kilometer of the marine crust at Deep Sea Drilling Project Hole 504B, eastern Pacific Ocean

Abstract: Deep Sea Drilling Project hole 504B is located in 5.9 m.y. crust in the eastern Pacific Ocean about 200 km south of the Costa Rica Rift. At 1076 m subbasement, it is the deepest penetration of marine crust yet achieved. We present here magnetic data from this hole, especially from the recently cored leg 83 section (which constitutes the lowermost 500 m). These data, when combined with those of other studies, yield not only the deepest but also the most detailed and comprehensive picture of marine magnetic stru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
76
0

Year Published

1989
1989
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 107 publications
(80 citation statements)
references
References 43 publications
4
76
0
Order By: Relevance
“…This may produce a declination error of about 17° estimated from McFadden et al (1988). This is similar to the standard deviation of the stable inclination of the sheeted dike complex (-23°, Smith and Banerjee, 1986;-17°, Dick, Erzinger, Stokking, et al, 1992). We consider that this controls the precision of our reorientations.…”
Section: Paleomagnetic Reorientationsupporting
confidence: 54%
See 1 more Smart Citation
“…This may produce a declination error of about 17° estimated from McFadden et al (1988). This is similar to the standard deviation of the stable inclination of the sheeted dike complex (-23°, Smith and Banerjee, 1986;-17°, Dick, Erzinger, Stokking, et al, 1992). We consider that this controls the precision of our reorientations.…”
Section: Paleomagnetic Reorientationsupporting
confidence: 54%
“…It is possible that some lithologic units are normally magnetized, but for the majority the assumption is probably valid. Smith and Banerjee (1986) have described a secondary magnetization in a few samples in the upper part of the dike sequence, which they used to identify the polarity of the stable remanence component. This yielded approximately equal numbers of reversed and normal polarities, although it was not clear whether this secondary component represented a component acquired in situ, in the Earth's field, or a later viscoremanent contamination.…”
Section: Paleomagnetic Reorientationmentioning
confidence: 99%
“…At least three processes can affect the magnetic properties of crustal rocks; low temperature oxidation/alteration of the magnetic minerals, geochemical variability and variations in geomagnetic field intensity. In axial and near axis locations extrusive basalts are assumed to comprise the majority of the magnetic source layer Smith and Banerjee, 1986;Pariso and Johnson, 1991]. The primary carrier of magnetic moment in basalts is titanomagnetite, which is altered to lower magnetic moment titanomaghemite Marshall and Cox, 1973;Pariso and Johnson, 1991].…”
Section: Source Of Variations In the Along-axis Camh Amplitudementioning
confidence: 99%
“…The deepest penetration of marine crust (at 1076 msub-basement) was achieved on DSDP hole 504B and low-temperature altered titanomagnetite was reported to be the dominant magnetic carrier (SMITH and BANERJEE, 1986). They showed that the NRM in the lower two sections was a chemical rather than a thermal remanence.…”
mentioning
confidence: 99%